Beyond Contracts: Love in Firms - Argandoña, Antonio 1943- (2011)
The traditional theories of the firm leave no room for love in business organizations, perhaps because it is thought that love is only an emotion or feeling, not a virtue, or because economic efficiency and profit making are considered to be incompatible with the practice of charity or love. In this article, we show based on an approach to the human action within the organization, that love can and must be lived in firms for firms to operate efficiently, be attractive to those who take part in them, and act consistently in the long run.
Keywords: Virtues; theory of the firm; Organization; Love; Firm; Charity; Action theory